The lymphatic system and COVID-19 vaccines - Miyasaka, Masayuki (Frontiers in Immunology, 2022)
Understanding the precise mechanism of vaccine-induced protection and the immune correlates of protection against coronavirus disease 2019 (COVID-19) is crucially important for developing next-generation vaccines that confer durable and protective immunity against COVID-19. Similar factors are also important for other infectious diseases. Here, I briefly summarize the mechanism of action of the currently used COVID-19 mRNA vaccines from the viewpoint of the function of the lymphatic system.